Radiologic assessment of the optimal point for tube thoracostomy using the sternum as a landmark: a computed tomography‐based analysis - Jaeik Jang; Jae-Hyug Woo; Mina Lee; Woo Sung Choi; Yong Su Lim; Jin Seong Cho; Jae Ho Jang; Jea Yeon Choi; Sung Youl Hyun (Journal of Trauma and Injury)
Purpose This study aimed at developing a novel tube thoracostomy technique using the sternum, a fixed anatomical structure, as an indicator to reduce the possibility of incorrect chest tube positioning and complications in patients with chest trauma. Methods This retrospective study analyzed the data of 184 patients with chest trauma who were aged ≥18 years, visited a single regional trauma center in Korea between April and June 2022, and underwent chest computed tomography (CT) with their arms down. The conventional gold standard, 5th intercostal space (ICS) method, was compared to the lower 1/2, 1/3, and 1/4 of the sternum method by analyzing CT images. Results When virtual tube thoracostomy routes were drawn at the mid-axillary line at the 5th ICS level, 150 patients (81.5%) on the right side and 179 patients (97.3%) on the left did not pass the diaphragm. However, at the lower 1/2 of the sternum level, 171 patients (92.9%, P<0.001) on the right and 182 patients (98.9%, P= 0.250) on the left did not pass the diaphragm. At the 5th ICS level, 129 patients (70.1%) on the right and 156 patients (84.8%) on the left were located in the safety zone and did not pass the diaphragm. Alternatively, at the lower 1/2, 1/3, and 1/4 of the sternum level, 139 (75.5%, P=0.185), 49 (26.6%, P<0.001), and 10 (5.4%, P<0.001), respectively, on the right, and 146 (79.3%, P=0.041), 69 (37.5%, P<0.001), and 16 (8.7%, P<0.001) on the left were located in the safety zone and did not pass the diaphragm. Compared to the conventional 5th ICS method, the sternum 1/2 method had a safety zone prediction sensitivity of 90.0% to 90.7%, and 97.3% to 100% sensitivity for not passing the diaphragm. Conclusions Using the sternum length as a tube thoracostomy indicator might be feasible.